Uji Resistensi Campylobacter sp. Yang Diisolasi Dari Rusa Timor (Rusa Timorensis) Terhadap Antibiotik - Jampur, Sesarius Wahyu Pagung; Tangkonda, Elisabet; Laut, Meity M (Jurnal Veteriner Nusantara, 2024)
Timor deer (Rusa timorensis) is a protected animal and is categorized as vulnerable in the International Union for Conservation of Nature of Threatened Species Red List (IUCN Red List). Efforts to save and prevent timor deer from extinction are through conservation in captivity. Captive-bred timor deer can be infected with Campylobacter sp. which is one of the causes of diarrhea in humans. Antibiotic resistance to Campylobacter sp. has been widely reported in various parts of the world. Timor deer are not directly exposed to antibiotics but can experience antibiotic resistance due to interactions with humans. The purpose of this study was to determine resistance and determine the level of resistance of Campylobacter sp. isolated from timor deer to antibiotics. This research was conducted using Campylobacter sp. isolates on modified charcoal-cefoperazone-deoxycholate agar (mCCDA) media. Kirby-Bauer method resistance test with Mueller-Hinton agar media using test antibiotics: ampicillin, ciprofloxacin, erythromycin, chloramphenicol, and tetracycline. Data were analyzed by looking at the inhibition zone formed and compared with Clinical and Laboratory Standards Institute (CLSI) standards. The results showed that Campylobacter sp. from timor deer had developed resistance to ampicillin, erythromycin, and tetracycline antibiotics. The inhibition zones formed from the five types of test antibiotics were ampicillin (7.58 mm), ciprofloxacin (26.76 mm), erythromycin (11.65 mm), chloramphenicol (24.40 mm), and tetracycline (9.05 mm).